Employment of accounting professionals: A descriptive analysis for Chile - Peña-Acuña, Verónica; Dote-Pardo, Jairo; Gutiérrez-Sandoval, Carolina; Betancourt-Betancourt, Camila (RAN - Revista Academia & Negocios, 2024)
Purpose: The objective is to descriptively analyze the employment of accounting professionals from a university in Chile, contrasting their situation with the national average. Methodology: The analysis employed frequency distribution tables, contingency tables, Chi-square tests, and correlation coefficients. Data were obtained from a survey administered to 184 accounting graduates between 2012 and 2021 from a university in Chile. Results: The findings indicate that employability is higher among graduates from the studied university; however, their gross income is lower compared to the national average. Implications: The results are useful for improving aspects of the curriculum to better align with current and future labor market trends for accounting professionals. Additionally, it calls for an exploration of the determinants that explain the employment situation, with the aim of identifying potential areas for professional development. Value: Although there are existing studies on the employability of accounting professionals, this work contrasts a local reality with the national average to identify differences that can be translated into curricular improvements and public employment policy to balance labor market conditions.